TRADISI MAGAYOT DALAM UPACARA NGENTEG LINGGIH DI PURA DALEM MAWOSPAHIT BANJAR TIBUBENENG KUTA UTARA KABUPATEN BADUNG (PERSPEKTIF PENDIDIKAN AGAMA HINDU) - I Wayan Widi Adnyana; I Nyoman Kiriana; I Made Dharmawan (Upadhyaya : Jurnal Penelitian Pendidikan, 2020)
Research on the Magayot Tradition in the Ngenteg Linggih Ceremonyat Pura Dalem Mawospahit Banjar Tibubeneng, North Kuta, Badung Regency is a tradition that is included in the ceremonyof Dewa Yadnya. Pamedek gratitude realized with the magayot tradition as a form of expression of gratitude for a big ceremony was held. This is very interesting to study because there are a shift in meaning, whichis a form of bargaining with God. Study This is carried out to answer the following problems: (1) How is the traditional process? Magayot in the Ngenteg Linggih Ceremony at the Dalem Mawospahit Temple Banjar Tibubeneng, North Kuta, Badung Regency? (2) What is the function of the Magayot Tradition in the Ngenteg Linggih Ceremony att he Dalem Mawospahit Temple Banjar Tibubeneng Kuta Northof Badung Regency? (3) What is the value of Hindu religious education contained in the Magayot Tradition in the Ngenteg Linggih Ceremony at Pura Dalem Mawospahit Banjar Tibubeneng, North Kuta, Badung Regency?. The theory that used to solve research problems is constructivism theory, theory functional, valuetheory. The resultsofthis study, the processor ritual of the Magayot Tradition in the Ceremony Ngenteg Linggih at Dalem Mawospahit tample Banjar Tibubeneng North Kuta Badung Regency is a Dewa Yadnya ceremony which is carried out on the the holding of the Ngenteg Linggih ceremony. Functions of the Magayot Tradition in Ceremonies Ngenteg Linggih at Dalem Mawospahit tample Banjar Tibubeneng North Kuta Badung Regency is a visualization of God's presence and attitude formation live. The educational value contained in the Magayot Tradition in the Ceremony Ngenteg Linggih at Dalem Mawospahit tample Banjar Tibubeneng North Kuta Badung Regency, namely ethical values, event values, magical religious values, moral values friendship, lifevalue, spiritual mental value.